Determinants of household food expenditure in Tanzania: Implications on food security - Ndakije Furaha R.; Sesabo,Jennifer K.; Lihawa, Robert M.; Mkuna, Eliaza (Agriculture &Food Security, 2024)
A research article submitted to the Agriculture & Food Security Journal, 2024.